2009
DOI: 10.1002/jbm.b.31517
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biological response to a self‐adhesive resin cement under different curing strategies

Abstract: Self-adhesive resin cements represents a new approach in indirect restorative dentistry, although little is known about its biological properties. The influence of the curing strategy on the biological response of a self-adhesive resin cement (Rely-X Unicem/3M ESPE) was evaluated through methyltetrazolium (MTT) and nitric oxide (NOx) assays. Cylindrical specimens (n = 48) were prepared and cured according to the following strategies: photoactivation with halogen light-curing unit (LCU) Demetron/Kerr, LED LCU R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…The increase of DC values of the reinforced cement influenced most of the other properties studied, as found in other studies [37,38,48]. In a general analysis, the addition of TiO 2 -nt in the evaluated self-adhesive resin cement positively influenced its properties, especially in the self-curing mode, which has an indication for use with certain limitations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The increase of DC values of the reinforced cement influenced most of the other properties studied, as found in other studies [37,38,48]. In a general analysis, the addition of TiO 2 -nt in the evaluated self-adhesive resin cement positively influenced its properties, especially in the self-curing mode, which has an indication for use with certain limitations.…”
Section: Discussionsupporting
confidence: 73%
“…However, the DCT group at 24 h showed a significant difference in cell viability when compared to CP. This result can be explained by the relationship between the type of polymerization employed and the DC obtained with regard to the cytotoxicity of resin cements [37]. The cements with lower DC showed a significant decrease in cell survival when compared to cements with the highest DC [38].…”
Section: Discussionmentioning
confidence: 99%
“…14 Several variables modulate RU cytotoxicity, depending, among other factors, on the curing strategy. 9 In the present study, the compatibility of RU after indirect pulp capping in deep cavities demonstrates that the remaining dentin, even if it is thin, can act as a barrier against the diffusion of possibly harmful chemical components in the material, thus avoiding direct contact of these components with the underlying connective pulp tissue and attenuating possible toxic effects. 29 Our findings support a previous in vitro investigation that used dentin disks to investigate the cytotoxicity of RU and found that more than 80% of cells remain viable after 24 hours or 7 days of indirect contact with the cement.…”
Section: Discussionmentioning
confidence: 58%
“…5 The mechanical, chemical and biological properties of KC and RU have been investigated previously. 4,6,7,8,9,10,11,12,13,14,15,16 Because most teeth that require prosthetic treatment exhibit extensive coronal damage, investigations of the biological tissue response induced by luting agents on teeth with pulp vitality are relevant to understand the mechanisms of inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These self‐adhesive cements have good moisture tolerance, release fluoride in a similar manner as glass ionomer cements (Radovic et al, ), do not require pretreatment of dentin with acid agents, and has been placed on deep dentin without producing an adverse pulpal response (Costa et al, ). Although a number of studies have evaluated the physicochemical and mechanical properties (Ernst et al, ; Escribano and De la Macorra, ; Holderegger et al, ) as well as the in‐vitro cytotoxicity (Bakopoulou et al, ; Monteiro et al, ; Ulker and Sengun, ) of the self‐adhesive resin cement Rely X™ Unicem, studies on the in‐vivo tissue response to this material are scarce (Costa et al, ) and further investigation is needed.…”
Section: Introductionmentioning
confidence: 99%